Nutrient-dense foods and diverse diets are important for ensuring adequate nutrition across the life course - Beal, Ty; Manohar, Swetha; Miachon, Lais; Fanzo, Jessica (National Academy of Sciences, 2024)
The world faces a global challenge of how to meet the nutritional needs of a diverse global population through diets. This paper defines the relative nutritional needs across each stage of the life cycle to support human health and identifies who is nutritionally vulnerable. Findings in this paper suggest that there are biological nutritional vulnerabilities stemming from high micronutrient needs per calorie in certain phases of the life cycle, particularly for infants and young children, women of reproductive age, pregnant and lactating women, and older adults, particularly older women. The paper demonstrates the role of micronutrient-dense animal-source foods and plant-source foods important in meeting essential nutrient needs to support healthy growth, development, and aging across vulnerable stages of the life cycle.